COOPERATIVE PRINCIPLE OF CONVERSATIONS IN VIKRAM SETH’S A SUITABLE BOY: A SOCIO-PRAGMATIC ASSESSMENT OF INFERENTIAL CHAINS OF INTERPRETATION - Thakur, Vijay Singh (UPI Press, 2016)
Grice (1975) provides an interpretative model that explains how we draw inferences from conversation. This theory of Cooperative Principle (CP), based on the philosophical ideas of Grice, relates the text to its contexts, including social context. As Schiffrin (1994) remarks, the application of CP to dialogic conversations leads to a particular view of discourse and its analysis, i.e. discourse as a text whose contexts (including cognitive, social and linguistic contexts) allow the interpretation of real speaker meaning in utterances (p. 227). The approach that Gricean Pragmatics offers to discourse analysis is based on a set of general principles about rationally-oriented communicative conduct that tells speakers and hearers how to organize and use information offered in a text, along with background knowledge of the world (including knowledge of the immediate social context), to convey (and understand) more than what is said– put simply, to communicate. In this paper, I am going to focus on and explore how we understand fictional discourse using pragmatic interpretative strategies to reconstruct inferential chains which lead us to a particular interpretation of conversation. I will discuss various issues of inferences, generated via Grice’s model, in the interpersonal pragmatics involved in the character utterances in Vikram Seth’s A Suitable Boy. The paper attempts to demonstrate how pragmatic interpretative strategies can make an added contribution to the study of literature as well as to the development of pragmatic competence, critical thinking, and better understanding of the use of naturally occurring language, both in literature and language classrooms.